STRATEGI PENGEMBANGAN KAWASAN AGROWISATA RURUKAN - Ireine Gratia Palit; Celcius ., Talumingan; Grace A. J. Rumagit (AGRI-SOSIOEKONOMI, 2017)
The purpose of this research is to identify the right strategy in developing Rurukan agro tourism area. The research location was conducted in two urban villages: Rurukan and Rurukan 1, East Tomohon Subdistrict, Tomohon City. This research was conducted for 3 (three) months from November 2016 to January 2017. The data used in this study are primary data and secondary data. Primary data are data taken through direct observation on site, interview with respondents who selected 10 people to fill out the research questionnaire as follows: Government (3 people), namely Lurah Rurukan, Lurah Rurukan One, and Officials of Tomohon City Tourism Office, Community Shop (2 persons) and Tour Manager (5 persons). Secondary data is data obtained from the offices of two urban villages and Tourism Office. The analytical method used SWOT Analysis. Based on the results of research and discussion, it can be concluded that the development strategy of Rurukan agro tourism area is Rapid growth strategy. This development strategy is in accordance with the position of Rurukan area that needs a progeny strategy to support growth, through several strategies that can be implemented, namely: (1) Utilizing some existing tourism object to attract investors so that it can become a growing tourism sector and interest in Tomohon ; (2) utilizing the famous agro tourism with its trademark to become a cultural development area, especially in Tomohon City; (3) utilizing a good soil fertility level in the Rurukan area to be planted with fruits such as strawberries, which are highland fruit trees to be enjoyed by tourists.